PENGEMBANGAN ALAT EVALUASI BERBASIS WORDWALL UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN PANCASILA - Anisa Bela Febriani; Hanif Amrulloh; Lutfi Fadilah (Universitas Islam Lamongan, 2025)
The selection of this evaluation tool has considerations. For example, learning materials, facilities or facilities available at school, so that the learning objectives that have been set can be achieved. This can be facilitated by developing a wordwall-based interactive learning evaluation tool on pancasila education subjects, material on pancasila values.”This research is“R&D research wich refers to the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model.